2008
DOI: 10.1007/s00421-008-0763-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ACTN3 R577X polymorphism with power athlete status in Russians

Abstract: The alpha-actinin-3 (ACTN3) gene encodes a Z-disc structural protein which is found only in fast glycolytic muscle fibers. A common nonsense polymorphism in codon 577 of the ACTN3 gene (R577X) results in alpha-actinin-3 deficiency in XX homozygotes. Previous reports have shown a lower proportion of the ACTN3 XX genotype in power-oriented athletes compared to the general population. In the present study we tested whether XX genotype was under-represented in Russian power-oriented athletes. The study involved 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
99
0
23

Year Published

2010
2010
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 17 publications
16
99
0
23
Order By: Relevance
“…Although sprint performance is likely a polygenic trait, only a few single nucleotide polymorphisms (SNP's), namely ACTN3 R577X [1][2][3][4], ACE I/D [5][6][7] and more recently eNOS -786 T/C [8] and, IL-6 -174G/C ( ), were found to be associated with sprint performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sprint performance is likely a polygenic trait, only a few single nucleotide polymorphisms (SNP's), namely ACTN3 R577X [1][2][3][4], ACE I/D [5][6][7] and more recently eNOS -786 T/C [8] and, IL-6 -174G/C ( ), were found to be associated with sprint performance.…”
Section: Introductionmentioning
confidence: 99%
“…Energy system contribution during 200-to 1500-m running in highly trained athletes, it can be assumed that the proportion of the Ser582 allele will be higher among sprinters compared to endurance athletes and sedentary controls. Therefore, the purposes of the present study were 1) to compare the frequency distribution of the HIF1A Pro582Ser (rs11549465) polymorphism between athletes of sports with different demands (endurance vs. sprinters) as well as between athletes of competitive levels (elite-level vs. national-level), and 2) to test the influence of the interaction between the HIF1A Pro582Ser and the ACTN3 R577X (rs1815739) genotypes, since the ACTN3 R577X polymorphism was previously reported to influence power-oriented top-level athletic performance in a broad variety of ethnic groups [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the RR genotype is over-represented in several groups of power-athletes (Druzhevskaya et al 2008;Eynon et al 2009e;Niemi and Majamaa, 2005;Yang et al 2003), with the overall conclusion that this specific genotype may confer an advantage in power-oriented sports events, e.g. sprint, jumping or throwing.…”
Section: Discussionmentioning
confidence: 99%
“…We genotyped six genetic SNPs in the PPARGC1A-NRF-TFAM pathway genes, which are known to be associated with endurance exercise performance capacity: (Eynon et al 2009d;He et al 2008); (iii) NRF2 C/T (rs8031031) (Eynon et al 2009a); (iv) peroxisome proliferator-activated receptor alpha (PPARA) intron 7 G/C (rs4253778) (Ahmetov et al 2006;Eynon et al 2009b); (v) peroxisome proliferator-activated delta (PPARD) C294T (Eynon et al 2009c); (Skogsberg et al 2003); and (vi) PPARGC1A Gly482Ser (Eynon et al 2009c;Lucia et al 2005). We also studied the ACTN3 R577X polymorphism, which is known to be associated with power-oriented performance (Druzhevskaya et al 2008;Eynon et al 2009e;Niemi and Majamaa, 2005;Yang et al 2003). The studied polymorphisms and genotypes of the Israeli endurance runner are presented in Table 2.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation